DIPLOMACY AND SOFT POWER: RELATIONSHIP AND MODERN SCIENTIFIC VIEW - Tursunova, Malikakhon (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This scientific thesis consistently reveals the meaning and modern understanding of diplomacy and soft power. It is important to recognize that today in a world complicated by many political ambitions and disagreements between the interests of states, the use of only "hard" methods of influence in the political arena is not enough, in connection with which, for several decades now, methods of manifestation in the foreign and domestic policies of states, soft power have been relevant. Often, with the help of such methods, more advantages are achieved. Accordingly, this thesis aims to reveal the manifestation of soft power in the diplomacy of different states, to reveal the general theoretical and legal aspects of the concept of soft power, and in all cases and by all states it can be applied in the practice of interstate relations. The final result of the scientific work will be conclusions and proposals aimed at a better scientific understanding of the use of soft power in diplomatic relations between countries.